PENDAPENDAMPINGAN PETANI DALAM PENYIAPAN PESTISIDA BIORASIONAL UNTUK PENGELOLAAN HAMA DAN PENYAKIT TANAMAN AGAR MENGHASILKAN SAYURAN BEBAS RESIDU BAHAN KIMIA DAN MENDUKUNG GREEN ECONOMYMPINGAN PETANI DALAM PENYIAPAN PESTISIDA BIORASIONAL UNTUK PENGELOLAAN HAMA DAN PENYAKIT TANAMAN AGAR MENGHASILKAN SAYURAN BEBAS RESIDU BAHAN KIMIA DAN MENDUKUNG GREEN ECONOMY - Nasir, Burhanuddin Haji; Serdiati, Novalina; Tangkesalu, Dance; Lasmini, Sri Anjar (Jurnal Abdi Insani, 2024)
The cultivation of vegetable crops carried out by the community in the Transmigration Settlement Unit (UPT) Palu Valley, Central Sulawesi has been going on for a long time, but has not been able to increase their income and welfare, due to various problems faced such as: low productivity of farming which is produced because it is cultivated on dryland, pest and plant disease attacks, difficulty in obtaining inorganic fertilizers and pesticides needed during farming, and group member participation in farmer group meetings to discuss various matters of common interest within the farmer group is very low.  The solution offered is to implement pest and disease control technology, organic fertilizer development technology and assistance in improving farmer group management. Community Partnership Empowerment aims to assist partner farmer groups in providing biorational pesticides made from local resources and improve management of farmer groups so that they can play an optimal role in helping farmer group members in various activities with local government. This community empowerment program was implemented at UPT Bulupountu Jaya, Sigi Biromaru District, Sulawsesi Tengah, from July to September 2024, by implementing community assistance methods to increase the knowledge and skills of participants as one of the efforts to empower partners. Implementation of training in the manufacture and development of biorational pesticides in the "Tani Mandiri" group can be adopted by participants because the method of manufacture is simple and easy to do. There are 3 types of plants that are made into botanical insecticides, namely vitex (Vitex negundo L), biduri (Callotropis gigantea L.) and kirinyuh (Cromolaena odorata L), while the biofungicide being developed is liquid trichoderma, as well as biological fertilizer made in the form of PGPR. The technology application demonstration plot shows that biorational pesticide application can reduce the intensity of pest and disease attacks on vegetable crops. The use of plant extracts as botanical insecticides and trichoderma biofungicides can reduce the intensity of pest and disease attacks on vegetable crops, so they can be used as an alternative to synthetic chemical pesticides.